2018
DOI: 10.3390/ijms19051287
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Splicing in Prostate Cancer

Abstract: Over 95% of human genes are alternatively spliced, expressing splice isoforms that often exhibit antagonistic functions. We describe genes whose alternative splicing has been linked to prostate cancer; namely VEGFA, KLF6, BCL2L2, ERG, and AR. We discuss opportunities to develop novel therapies that target specific splice isoforms, or that target the machinery of splicing. Therapeutic approaches include the development of small molecule inhibitors of splice factor kinases, splice isoform specific siRNAs, and sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 155 publications
2
13
0
Order By: Relevance
“…Small molecule inhibitors have been successfully employed to target splicing factors, splicing factor kinases, or upstream splicing regulators and to alter mRNA splicing patterns. Likewise, siRNAs and SSOs have also been applied to specifically target and disrupt the splicing regulatory sequences or splicing factor/RNA interactions at the pre-mRNA level [ 188 , 189 ]. SF3B1-targeting agents, such as spliceostatins, pladienolides and herboxidienes, are small molecule inhibitors used to disrupt the early stage of spliceosome assembly [ 188 ].…”
Section: Therapeutic Strategies For Correcting Aberrant Splicing Ementioning
confidence: 99%
See 1 more Smart Citation
“…Small molecule inhibitors have been successfully employed to target splicing factors, splicing factor kinases, or upstream splicing regulators and to alter mRNA splicing patterns. Likewise, siRNAs and SSOs have also been applied to specifically target and disrupt the splicing regulatory sequences or splicing factor/RNA interactions at the pre-mRNA level [ 188 , 189 ]. SF3B1-targeting agents, such as spliceostatins, pladienolides and herboxidienes, are small molecule inhibitors used to disrupt the early stage of spliceosome assembly [ 188 ].…”
Section: Therapeutic Strategies For Correcting Aberrant Splicing Ementioning
confidence: 99%
“…H3B-8800, another splicing modulator targeting SF3B1, inhibits expression of aberrant splice variant MAP3K7 in a dose-dependent manner and preferentially kills epithelial and hematologic malignancies expressing mutant spliceosome components [ 191 ]. Besides splicing factors ( Figure 4 A), the targeting of splicing factor kinases, such as the CDC2-like kinases (CLKs) and serine-arginine protein kinases (SRPKs), has emerged as a potential therapy to reverse aberrant RNA splicing [ 188 , 189 ]. For example, small molecule inhibitor SRPIN340 blocks SRPK1-mediated phosphorylation of SRSF1 [ 192 ], leading to splice switching of pro-angiogenic VEGFA165 to anti-angiogenic VEGFA165b in prostate cancer and leukemic cells [ 193 , 194 ].…”
Section: Therapeutic Strategies For Correcting Aberrant Splicing Ementioning
confidence: 99%
“…Characterization of the AS landscape in cancers via reliable big data to identify biomarkers provides a wealth of insight into cancers with excellent prognostic value. Hence, increasing evidence has indicated that AS is actively involved in the initiation, progression and prognosis of cancers [4,5]. Additionally, cancer researchers realize the significant clinical utility of AS and its potential as a useful therapeutic signaling target [68].…”
Section: Introductionmentioning
confidence: 99%
“…In prostate cancer, our area of interest, the most notable splicing change is the emergence of the ligand-independent androgen receptor ARV7 isoform in response to hormone deprivation (3). Other examples include proangiogenic splice variants of VEGFA (4), tumorigenic variants of the transcription factors ERG and KLF6 (5,6), and antiapoptotic splicing of BCL2L2 (7,8). However, the intersection of upstream oncogenic signaling, pre-mRNA splicing, and the biological processes affected by those splicing events has not been defined at a global level.…”
mentioning
confidence: 99%